(untitled) (Research, Society and Development, 2021)
Dengue fever is a contagion caused by a systemic virus, of which the main transmitter is the aedes aegypti mosquito, with excellent adaptation to the tropical and subtropical climate. This infectious disease has enormous relevance to public health because it is directly related to economic inequality and inappropriate life situations. This paper seeks to identify the factors associated with the occurrence of dengue and the preponderance that structural inequality causes in society. A mathematical method was used to calculate the increase and decrease of cases in the years 2015 to 2020, and to identify the epidemic peaks in each Brazilian state and Federal District. Twenty-seven peaks of the epidemic were calculated, and in the period scale, the greatest eventuality was confirmed in the years 2015, 2016, 2019 and 2020, in due order. Some states present a situation conducive to dissemination, causing high increases in dengue cases in Brazil.